Pneumococcal Immunization Reduces Neurological and Hepatic Symptoms in a Mouse Model for Niemann-Pick Type C1 Disease - Houben, Tom; Magro dos Reis, Inês; Oligschlaeger, Yvonne; Steinbusch, Hellen; Gijbels, Marion J. J.; Hendrikx, Tim; Binder, Christoph J.; Cassiman, David; Westerterp, Marit; Prickaerts, Jos; Shiri-Sverdlov, Ronit (Frontiers in Immunology, 2019)
Niemann-Pick type C1 disease (NPC1) is caused by a deleterious mutation in the Npc1 gene, causing lysosomal accumulation of unesterified cholesterol and sphingolipids. Consequently, NPC1 patients suffer from severe neurovisceral symptoms which, in the absence of effective treatments, result in premature death. NPC1 patients display increased plasma levels of cholesterol oxidation products such as those enriched in oxidized low-density lipoprotein (oxLDL), a pro-inflammatory mediator. While it has been shown that inflammation precedes and exacerbates symptom severity in NPC1, it is unclear whether oxLDL contributes to NPC1 progression. In this study, we investigated the effects of increasing anti-oxLDL IgM autoantibodies on systemic and neurological symptoms in an NPC1 mouse model. For this purpose, Npc1nih mice were immunized with heat-inactivated S. pneumoniae, an immunogen which elicits an IgM autoantibody-mediated immune response against oxLDL. Npc1nih mice injected with heat-inactivated pneumococci displayed improved hepatosplenic phenotypes, including liver lipid accumulation and inflammation. In addition, regression of motor skills was delayed in immunized Npc1nih. In line with these results, brain analyses showed an improved cerebellar phenotype in comparison with control-treated subjects. The improvements in neurodegeneration following immunization were accompanied by reduced neuroinflammation, as assessed by decreased expression of inflammatory markers and a reduction in cortical immune cell infiltration. This study highlights the potential of the pneumococcal immunization as a novel therapeutical approach in NPC1. Future research should investigate whether implementation of this therapy can improve life span and quality of life of NPC1 patients.